Reorientation and rocket launchers? Regional insights into Russia's wartime economy - Vesala Lauri (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This policy brief examines regional economic development in Russia since the brutal invasion of Ukraine in February 2022. We focus on the logistics, construction, and industrial sectors as they are closely related to the structural changes in Russia's economy due to the war and sanctions. We examine available regional-level statistics concerning these sectors and form hypotheses for the regional variation observed. We also utilize official Russian publications and news items. We find that the shift in Russia's trade flows and sanctions related to trade logistics have had a limited effect on rerouting trade. This seems largely due to the constraints of existing infrastructure, logistical bottlenecks, and the robustness of Russian oil export volumes. Barring a few regions, infrastructure development related to the reorientation of the economy has no noticeable impact on construction. Construction growth in regions bordering Ukraine is driven by war-related construction. Militaryindustrial production seems to be the national driver for most fast-growing industrial sectors. Regional-level data reflects this high growth in many traditional military-industrial hubs.
urn:nbn:fi-fe20230919132122
Keywords: 330; Russia; regional economic development; logistics; trade; infrastructure; construction; industry; military industry; Ukraine; Russia-Ukraine war